Toleransi dan pluralisme dalam kehidupan masyarakat kampung bugis tuban, kabupaten badung, bali - Irzam Fabiansyah, Achmad Khafid (Maliki Interdisciplinary Journal, 2026)
This study examines the implementation of tolerance and pluralism in the life of the Bugis Village community in Tuban, Badung Regency, Bali. Kampung Bugis Tuban is a Muslim community of Bugis descent that has lived harmoniously alongside the Balinese Hindu community since the 17th century. This study aims to analyze the forms of social tolerance, daily practices of pluralism, supporting factors, and challenges in maintaining interreligious harmony within a multicultural society. The method used is a descriptive qualitative approach by utilizing data from various literature sources and previous studies. The findings indicate that tolerance in Kampung Bugis Tuban is reflected through respect for religious traditions, participation in customary security activities, the tradition of ngejot, cooperation, and harmonious interfaith social interactions. Key factors supporting tolerance include the local cultural values of Tri Hita Karana, the historical relationship between the Bugis community and the Kingdom of Badung, as well as the contributions of the government, traditional leaders, and religious figures. However, globalization, the advancement of digital media, and the declining understanding of pluralism among younger generations pose challenges to maintaining social harmony. Therefore, strengthening multicultural education, interfaith dialogue, and the preservation of local cultural values are necessary to sustain tolerance and pluralism. Kampung Bugis Tuban can serve as a model of harmonious interreligious coexistence for Indonesia’s diverse society.